Metode Pembaruan Hukum Keluarga Islam Kontemporer - Khoiruddin Nasution (Unisia, 2007)
This article shortly discusses ‘ushul al-fiqh’ theories developed by prominent scholars, especially those related to two concepts: conventional and contemporary. These appear in relation to contem- porary Islamic Family Law reform in the form of codification. In determining legal status of a prob- lem, in some cases, only one of the concepts is usually used. However, in many cases, combina- tion of two or more concepts is used. In case of polygamy, for example, both concepts require fairness and capable for men to be allowed polygamy. Yet, to guarantee such fairness, contempo- rary concept requires more concrete criteria, such as fairness in distribution of properties. Keywords: ushul al-fiqh, Islamic Family Law, reform, conventional, contemporary.